2005
DOI: 10.1510/icvts.2005.117697
|View full text |Cite
|
Sign up to set email alerts
|

Does a percutaneous tracheostomy have a lower incidence of complications compared to an open surgical technique?

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was which method of tracheostomy had fewer complications, the surgical or percutaneous technique. A total of 264 papers were identified of which 13 provided the best evidence to answer the question. The author, journal, date and country of publication, patient group, relevant outcomes and weaknesses were tabulated. We conclude that both percutaneous and surgical tracheostomy have overall a low incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…7,9 Most of the tracheostomies are performed electively, while few are done as an emergency procedure. 10 In our series of 100 cases too, 73% were elective and 27% were performed as an emergency procedure. Common indications for elective tracheostomy include prolonged ventilator dependence, tracheal toileting and foreign body aspiration, while emergency tracheostomy is performed for upper airway obstruction due to laryngeal neoplasms, maxillofacial or laryngeal trauma, burns and upper airway infection.…”
Section: Discussionmentioning
confidence: 70%
“…7,9 Most of the tracheostomies are performed electively, while few are done as an emergency procedure. 10 In our series of 100 cases too, 73% were elective and 27% were performed as an emergency procedure. Common indications for elective tracheostomy include prolonged ventilator dependence, tracheal toileting and foreign body aspiration, while emergency tracheostomy is performed for upper airway obstruction due to laryngeal neoplasms, maxillofacial or laryngeal trauma, burns and upper airway infection.…”
Section: Discussionmentioning
confidence: 70%
“…In other study in Bangladesh this complications for elective tracheostory was 9.99% & emergency tracheostomy was 33.35% 3 . Study of Goldenberg D reported complications were more common in cases of emergency tracheostomy (43.26%) than elective (17.8%), total complications was 39.05% 10 .…”
Section: Discussionmentioning
confidence: 97%
“…In other study surgical emphysema was commonest complications both for elective (3.33%) & emergency tracheostomy (10%) 3 In another study. Rates of surgical emphysema and in elective tracheostomy as, 5% 9 , complications surgical emphysema is the commonest complication followed by haemorrhage 10 . These findings are consistent with results of this study however the rates of these complications differ from the other study 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a tracheostomy should be avoided within 2 weeks after open-heart surgery because of the high risk of mediastinitis [140][141][142][143][144][145][146][147][148]. On the other hand, high tracheostomy or percutaneous tracheostomy through the cricothyroid membrane is reported to reduce the risk of mediastinitis.…”
Section: Tracheostomy In Postoperative Crisismentioning
confidence: 99%